Scenic walks of the world : Disc 1 Our Dramatic Planet - Reader's Digest Association; Travel Channel (Firm); Questar, Inc. (Pleasantville, N.Y. Reader's Digest Association Chicago, Ill. Distributed by Questar, 2008)
Collection of programs presenting scenic walks through the world's landscapes, experiencing natural and man-made wonders, from New Zealand to Ireland, Machu Picchu to the hot springs of Alaska, and more.
1 1. Our dramatic planet (ca. 70 min.)
Some episodes originally produced for broadcast on the Travel Channel in 2007.
"Explore natural and man-made treasures on foot and up close"--Container
No additional credits.
DVD.
Language: English.
112453
Keywords: Trails; Great Pyramid (Egypt) -- Description and travel; Voyages and travels; Travelogues (Motion pictures); Voyages; journeys; Travel; Trails; Grand Canyon (Ariz.) -- Description and travel; Grand Canyon (Ariz.) -- Descriptions et voyages; New Zealand; Africa (Kilimanjaro); Travelogues (Motion pictures, television, etc.); Videorecording